Implementation of the Electronic Performance Programme in the Personnel and Legal Subdivision at the Regional Finance and Assets Agency of North Sulawesi Province - Itje Pangkey,; Thelma Wawointana,; Marseli A. Mantiri,; Novel S. Assa, (Technium Social Sciences Journal, 2023)
This research aims to find out and describe the Implementation of the Performance Electronic Program (E-Performance) in the Personnel and Legal Sub Division in the Regional Financial and Asset Agency of North Sulawesi Province. The research method used is descriptive Qualitative. Data collection uses Observation, Interview, and Documentation techniques. Data analysis through Data Reduction, Data Presentation and Conclusion withdrawal. The result showed that the Implementation of the Performance Electronic Program (E-Performance) in the Personnel and Legal Sub Division in the Regional Financial and Asset Agency of North Sulawesi Province, it can be concluded that it has not been effective.